Differentiation of Patients with Symptomatic Low von Willebrand Factor from Those with Asymptomatic Low von Willebrand Factor - Grabowski, Eric F.; Van Cott, Elizabeth M.; Bornikova, Larissa; Boyle, Daniel C.; Silva, Raisa Lomanto (Thrombosis and Haemostasis, 2020)
Background Accurate diagnosis of symptomatic low von Willebrand factor (VWF) remains a major challenge in von Willebrand disease (VWD). However, present tests do not adequately take into account flow forces that, at very high shear rates, reveal a weakness in the VWF-platelet glycoprotein glycoprotein Ib bond in normal subjects. The degree of this weakness is greater in symptomatic, but not asymptomatic, low VWF.Objective The aim of this study is to distinguish patients with symptomatic low VWF (levels in the 30–50 IU/dL range) from those with asymptomatic low VWF and normal subjects.Methods We measured platelet adhesion (PA)/aggregation in our novel microfluidic flow system that permits real-time assessment of PA (surface coverage) and PA/aggregation (V, aggregate volume) using epifluorescence digital videomicroscopy in flowing noncitrated whole blood at 4,000 second−1. Blood samples from 24 low VWF patients and 15 normal subjects were collected into plastic tubes containing 4 U/mL enoxaparin. MetaMorph software was used to quantify rates of PA and V increase.Results Rates of PA increase showed a bimodal distribution, with values for 16/24 patients (Group I) all below the 2.5th percentile of normal, and values for 8/24 patients (Group II) similar to controls. Bleeding scores (mean ± standard error) were 5.50 ± 0.45 versus 2.75 ± 0.45 (p = 0.00077), and 10 clinically significant bleeding events were observed in seven versus zero (p = 0.0295) Group I and Group II subjects, respectively.Conclusion The present approach may offer a definitive means to distinguish symptomatic low VWF from either asymptomatic low VWF or normal controls.
Keywords: von Willebrand disease; platelet aggregation; microfluidics; platelet function tests; von Willebrand factor